2016
DOI: 10.3390/su8111167
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Design Solutions in the Automotive Field: Environmental Modelling Based on Fuel Reduction Value Applied to Diesel Turbocharged Vehicles

Abstract: A tailored model for the assessment of environmental benefits achievable by "light-weighting" in the automotive field is presented. The model is based on the Fuel Reduction Value (FRV) coefficient, which expresses the Fuel Consumption (FC) saving involved by a 100 kg mass reduction. The work is composed of two main sections: simulation and environmental modelling. Simulation modelling performs an in-depth calculation of weight-induced FC whose outcome is the FRV evaluated for a wide range of Diesel Turbocharge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Indeed, using lightweight materials for vehicle manufacturing has been significantly successful compared to using biofuels (5%) [161]. The light-weighting policy unanimously has fewer trade-offs in adoption of novel and new materials and technologies [160,165]. Lightweight vehicles use aluminium, magnesium alloy, carbon-fibre reinforced polymer (CFRP) and other materials, which have lower GHG and CO 2 emissions over vesicle's life-cycle than iron and steel [165][166][167].…”
Section: Vehicle Light-weighting and Life Cycle Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, using lightweight materials for vehicle manufacturing has been significantly successful compared to using biofuels (5%) [161]. The light-weighting policy unanimously has fewer trade-offs in adoption of novel and new materials and technologies [160,165]. Lightweight vehicles use aluminium, magnesium alloy, carbon-fibre reinforced polymer (CFRP) and other materials, which have lower GHG and CO 2 emissions over vesicle's life-cycle than iron and steel [165][166][167].…”
Section: Vehicle Light-weighting and Life Cycle Assessmentmentioning
confidence: 99%
“…The light-weighting policy unanimously has fewer trade-offs in adoption of novel and new materials and technologies [160,165]. Lightweight vehicles use aluminium, magnesium alloy, carbon-fibre reinforced polymer (CFRP) and other materials, which have lower GHG and CO 2 emissions over vesicle's life-cycle than iron and steel [165][166][167]. For example, replacing steel Mg has led to 5.7% weight reduction that decreases the vehicle fuel consumption and life cycle emissions by 1.3% and 0.8%, respectively.…”
Section: Vehicle Light-weighting and Life Cycle Assessmentmentioning
confidence: 99%
“…Exergetic evaluation of H 2 FC buses have also been conducted [16]. Work on effects of light weighting has also been performed for automotive applications [17,18] as well as dealing with the challenges for modelling and integrating of light weighting into concept design [19]. However, there are no studies available on the effects of light weighting in relation to buses in general and H 2 FC buses in particular.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, physical and empirical methods were usually considered in modeling fuel consumption and emission. It was found that, vehicle fuel consumption and emission rates were usually associated with cruise speed, drivers' acceleration aggressiveness, road grade [1][2][3][4], traffic control strategies [5], and characteristics of a vehicle, e.g., weight [6][7][8].…”
Section: Introductionmentioning
confidence: 99%